(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the effectiveness of Hoat Huyet Nhat Nhat in reducing pain and improving quality of life in patients with primary dysmenorrhea. Methods: A randomized, double-Blind, placebo - controlled trial on 100 patients diagnosed with primary dysmenorrhea. Participants were randomly assigned to two groups: 50 received Hoat Huyet Nhat Nhat and 50 received placebo, for three consecutive menstrual cycles. Outcomes were assessed using the Visual Analog Scale (VAS) for pain intensity, duration of pain, rescue Naproxen consumption, and quality of life measured by EQ-5D-5L. Results: In the Hoat Huyet Nhat Nhat group, mean VAS score decreased from 6.72 ± 1.14 to 4.14 ± 2.08 (p < 0.01), mean pain duration reduced from 18.9 ± 6.88 to 10.82 ± 7.86 hours (p < 0.01), and mean Naproxen consumption was significantly lower (4.0 ± 2.1 mg vs. 9.5 ± 3.4 mg in the placebo group, p < 0.01). Quality of life improved significantly with EQ-5D-5L increasing from 0.52 ± 0.18 to 0.80 ± 0.18 (p < 0.01), while the placebo group showed no significant changes. Conclusion: Hoat Huyet Nhat Nhat is effective in reducing menstrual pain, shortening pain duration, lowering the need for rescue analgesics, and improving quality of life in patients with primary dysmenorrhea. It is a safe and feasible therapeutic option for clinical practice.